Formação e a prática dos orientadores pedagógicos do Colégio Catarinense: impasses, possibilidades e desafios - Passos, Rodrigo dos (Universidade do Vale do Rio dos Sinos, 2016)
The job of pedagogical guidance has required the professionals who act in this role a great demand of work. Although it seeks a better relationship between teaching and learning, the great demand does not allow them to perform their function the way they would like to or realize as essential. Thus, the present study sought to identify the challenges and possibilities faced on a daily basis by a group of pedagogical advisors which is part of the Educational Guidance Service of Catarinense School, in Florianópolis, SC. This team consists of five people that drive an average of 20 teachers each. The group of pedagogical advisors was accompanied in some meetings and individual interviews were carried out with the intention of listening to them in order to register and submit suggestions for improvements to the professional practice . Alarcão, Arroyo, Freire, Hypólito, Luck, Morin, Nóvoa, Paro, Rios, Saviani e Tardif contributed to give theoretical support to this research. The investigation found that even though the pedagogical advisors did not have specific initial training to the exercise of the function, they have a great sensitivity to the demands of their teachers. They realize that there is a gap between the practice pedagogical tutoring and what they aim in theory. The advisors recognize the specificity of knowledge to professional practice and the limits of their training, trying to supply the teachers individually or in institutional initiatives. They also carry out actions which can be summarized in: a) didactic pedagogical support; b) pedagogical work organization; c) mediation between different instances; and d) project booster. However, the bureaucratic demands have filled most of the advisors time, and the pedagogical training quality they aim, which is the core of the work, has not always been possible to be achieved. Teachers confirm the infrastructural quality of the institution and bet on its potential openness to change. The readings and discussions undertaken show that we need a new perspective on this service in school, improving it so that every meeting between teacher and guidance counselor is a moment of study and shared reflection about the pedagogical practice.
Keywords: Orientação pedagógica; Desafios dos orientadores pedagógicos; Teoria e prática na orientação; Pedagogical guidance; Counselor’s challenges; Theory and practice in guidance; ACCNPQ::Ciências Humanas::Educação